Pengaruh Sistem Akuntansi Keuangan Daerah, Kualitas Sumber Daya Manusia, Sistem Pengendalian Intern terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Nur Isnaini Machmudiyanti; Muhammad Aufa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to examine the influence the application of regional financial system, the quality of human resources, and the application of internal control system to the quality of local government financial reports. This type of research is quantitative research by distributing questionnaires. The theory used in this study is the stewardship theory. The sampling method in this tudy was the purposive sampling method. The sample in this study is the staff/employees BPPKAD Gresik were 46 respondents. The analytical method used is multiple linear regression analysis using the IBM SPSS Statistic 22 Program. The result of this study indicate that the influence the application of regional financial system has a significant influence and the quality of local government financial reportsand the quality of human resources, application of internal control system partially does not have a significant influence on the quality of local government financial reports.